2006
DOI: 10.1038/sj.jid.5700209
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Loss at Drosophila Patched Gene Is Highly Prevalent in Basal and Squamous Cell Carcinomas of the Skin

Abstract: The human homolog of the Drosophila Patched gene (PTCH), located at chromosome 9q22.3, is frequently altered in both nevoid basal cell carcinoma syndrome, and sporadic basal cell carcinomas (BCCs). However, alteration of the PTCH gene locus has been poorly studied in squamous cell carcinoma (SCC). We analyzed loss of heterozygosity (LOH) at five markers in and around the PTCH gene in 276 keratinocyte tumors from a population-based study in New Hampshire. We found a high prevalence of any 9q22.3 LOH in both BCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 39 publications
2
21
0
1
Order By: Relevance
“…0.08). Overall, these data support the hypothesis that loss of PTCH is a common, early lesion for SCC and BCC [82] , and that chromosomal alterations in certain gene loci might be used as biomarker for UV (sun) exposure in the past [for example, if they appear in persisting epidermal (stem) cells].…”
Section: Markers Of Altered Structure/functionsupporting
confidence: 66%
See 1 more Smart Citation
“…0.08). Overall, these data support the hypothesis that loss of PTCH is a common, early lesion for SCC and BCC [82] , and that chromosomal alterations in certain gene loci might be used as biomarker for UV (sun) exposure in the past [for example, if they appear in persisting epidermal (stem) cells].…”
Section: Markers Of Altered Structure/functionsupporting
confidence: 66%
“…The human homolog of the Dro-sophila patched gene (PTCH) , located at chromosome 9q22.3, is frequently altered in both nevoid BCC syndrome and sporadic BCCs. Danaee et al [82] also studied alterations of the PTCH gene locus in SCC. They analyzed LOH at 5 markers in and around the PTCH gene in 276 keratinocyte tumors and found a high prevalence of a LOH at 9q22.3 in both BCC (75.5%) and SCC (60.8%).…”
Section: Markers Of Altered Structure/functionmentioning
confidence: 99%
“…The prevalence of LOH was 50% for BCC, and 27.27% for OC. In literature the prevalence of LOH in BCCs is between 35 and 75% (40,22,41,42,26) and 70% for ovarian tumors, both benign and malignant (30). Our data is comparable with published data for BCC, but is significantly lower for OC.…”
Section: Discussionsupporting
confidence: 81%
“…Sporadic mutations of the PTCH1 gene are involved in a series of sporadic tumors, including BCC (21,22), medulloblastomas (23), skin trichoepitheliomas (24), esophageal squamous cell carcinomas (25), squamous cell carcinomas (26), breast cancer (23), as well as in odontogenic keratocysts (27).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies (9)(10)(11)(12), as well as others (13)(14)(15), have revealed that >85% of NBCCS-associated KCOTs and nearly 30% of sporadic KCOTs harbored PTCH1 mutations. In addition, loss of heterozygosity (LOH) at chromosome 9q22-31, the region to which the PTCH1 gene maps, has been observed as a frequent event in NBCCS-associated tumors, although different estimates of the prevalence of LOH (16-75%) were reported (8,(16)(17)(18). Besides, research on NBCCS-related primitive neuroectodermal tumors has shown that PTCH1 mutations occurred predominantly in tumors with LOH at 9q22 (17).…”
mentioning
confidence: 99%